Cardiovascular disease essential medicines listing by countries: changes over time and association with health outcomes - Camila Heredia; Moizza Zia Ul Haq; Adelaide Buadu; Amal Rizvi; Aine Workentin; Navindra Persaud (BMC Cardiovascular Disorders)
Abstract Background Since national essential medicine lists guide the procurement of medicines for populations in many countries, and cardiovascular diseases are the leading cause of death globally, including cardiovascular medicines on these lists can significantly impact healthcare outcomes. Methods In this cross-sectional study, national essential medicines’ lists from 158 countries were analysed on whether or not they included medicines to treat ischemic heart disease, cerebrovascular disease, and hypertensive heart disease. A linear regression model was used to evaluate the association between countries’ coverage scores and amenable mortality. Results Listing of cardiovascular disease treatment was associated with amenable mortality from hypertensive heart disease. Health expenditure per capita was also associated with amendable mortality due to ischemic heart disease, and hypertensive heart disease. Conclusions Listing essential medicines for cardiovascular disease is an important aspect of healthcare quality that is associated with cardiovascular mortality.